Pengaruh Tanggung Jawab Sosial Perusahaan terhadap Manajemen Laba menggunakan Karakteristik Dewan Komisaris Sebagai Variabel Pemoderasi - Fiola Finomia Honesty (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2020)
This study examines the nature and significance of the moderating effect of board of commisioners characteristics on the relationship between the disclosure of corporate social responsibility and earnings management. Using a sample of 30 manufacturing companies listed in the Indonesia Stock Exchange overs the period of 2010-2015, the results show that the disclosure of corporate social responsibility significantly affect earnings management. While board of commisioners characteristics which are board educational background and frequency of board meetings strengthen the relationship between the corporate social responsibility disclosure and earnings management